Is the EU-Turkey Action Plan an effective or just an apparent solution to the refugee crisis? - Carmen Moldovan (CES Working Papers, 2017)
European Union and its Member States have tried at least at political level to solve the problem of migrants and refugees inflows coming to Europe from the Middle East trough Turkey and Greece. Latest attempts in this regard are represented by the 2015 European Union-Turkey Action Plan and the 2016 Statement of the European Union and Turkey which contained measures aimed to control the irregular migration and human trafficking acts, in accordance with the European Union law and international standards of refugee law. Although the aforementioned acts refer to concrete provisional and extraordinary measures concerning different categories of persons arriving in Greece and applying for asylum and they were actually put in practice by Turkey, their legally binding force is controversial in the context of the recent interpretation of the Court of Justice of the European Union in some similar cases, in which the Court found that the 2016 Statement is not an act concluded by the institutions of the European Union and it is not an agreement legally binding. In other words, it represents a political statement which is excluded from the legality examination of the Court. Although the decision of the Court may be legally correct for procedural reasons, this situation raises questions concerning the commitment of the European Union and its institutions to really analyse and find effective measures regarding persons arriving in the European Union territory and claiming international protection according to international standards. The aim of this paper is to analyse the legal implications of the 2015 Joint Action Plan and the 2016 Statement and their compatibility with the international legal standard of refugees and to show the lack of resilience in adapting to refugee and irregular migration problems, contrary to the European Union values and principles.
Keywords: 330; political statement; legal effects; refugees; migration; jurisdiction